Struktur Pendapatan Rumah Tangga Tani Sekitar Perkebunan Kelapa Sawit (Studi Kasus di Desa Kersik Belantian Kecamatan Jelimpo) - Aliung, Aliung; Sudrajat, Jajat; Fitrianti, Wanti (Universitas Galuh, 2025)
The objective of this research is to analyze the household income structure of farmers residing around the oil palm plantations in Kersik Belantian Village, Jelimpo District. Data collection techniques were carried out through interviews, observations, and questionnaires to 43 farmer households. This research was conducted in a descriptive quantitative manner to calculate and describe the conditions of the income sources of farmers around the oil palm plantations. The data processing results show that income from the agricultural sector, particularly from on-farm oil palm activities, plays a central role in the economy of farmer households in Kersik Belantian Village. The sale of fresh fruit bunches (FFB) of oil palm is the main source of income, driven by large land areas and high productivity. However, reliance on oil palm also has a significant impact on income diversification, with non-oil palm and off-farm income becoming important as additional income that reduces the risk of price fluctuations and decreases in oil palm production. Additionally, the non-farm sector also makes a vital contribution to household income, with additional jobs outside of agriculture providing the necessary economic stability to face uncertainties in the on-farm sector. Although on-farm oil palm activities provide substantial economic benefits, high dependency also carries economic and environmental risks, emphasizing the importance of income diversification to maintain economic and environmental sustainability in the future. Therefore, efforts to reduce dependence on oil palm and increase income diversification should be a focus in the economic development planning of Kersik Belantian Village.